Reply: Prof. Ulrich Weidmann - Ulrich Weidmann (European Journal of Transport and Infrastructure Research, 2007)
The Fast Transit on Request (FTR) vision is enticing: a very comfortable bus bringing each passenger rapidly, directly and comfortably to their destination - no annoying waiting and transferring necessary! Unfortunately, the concept has the following problems when viewed holistically.